Effects Of Blood Lead, Smoking Habits And Nutritional Status Toward Cystatin C Serum (International Journal of Scientific Research and Management (IJSRM), 2015)
Raw pigments materials typically used powder and aluminum paste containing 60% of FeO, ZnO, Zn; 27% of Pb and Crcontaining compound; and 13% other compounds Using spray paint commonly found in a variety of industries, such as automobile painting industry. The aim of research to analyze the effects of blood lead, smoking habits and nutritional status of the cystatin C serum. This study is observational with cross sectional study. The population in this study is exposed and unexposed groups with each 12 samples of each group. Analysis of data using multiple linear regressions. Results showed no effect of blood lead with Cystatin C (β = 0.374 p =0.044), there was the influence of nutritional status and serum cystatin C (β=0.604 p=0.001), there was no effect of smoking and serum cystatin C (β = - 0.265: p = 0.164). The results showed that the serum level of Cystatin C is affected by blood lead levels and nutritional status while smoking habit there is no relationship.